Postoperative pain intensity and incidence following single visit root canal treatment with different obturation techniques: a randomized clinical trial - Koçer, Aliye; Dönmez Özkan, Hicran; Turk, Tugba (PeerJ, 2022)
Background There are few studies in the literature about the effect of obturation techniques on postoperative pain. Besides, GuttaFlow2 was used for the first time in this study regarding postoperative pain. This study aimed to compare the postoperative pain levels and incidence following single-visit root canal treatment with different canal filling techniques; cold lateral compaction (CLC), thermoplasticised solid-core carrier (GuttaCore) based filling and cold free-flow compaction (GuttaFlow2) technique. Methods The patients (n = 93) having single-rooted teeth with a single canal diagnosed with asymptomatic irreversible pulpitis or single-rooted vital teeth with a single canal requiring endodontic treatment because of prosthetic reasons were enrolled in this study. Patients were randomized into three groups (n = 31) according to the obturation technique. A single operator performed all the treatments in a single visit. Data on obturation levels, postoperative pain and analgesic intake frequency were recorded at postoperative 6, 12 and 24 h and daily afterward until the 7th day. Postoperative pain was measured by visual analogue scale (VAS). The date were statistically analyzed with chi-squared tests (for the analyses of the categorical data), the nonparametric Kruskal-Wallis test (for the comparisons of VAS score) and with the Friedman test (for the assessments of the changes in VAS scores over time). Results The GuttaCore group recorded the higher pain levels, except first 12 h, on the other hand, the GuttaFlow2 group recorded the lower pain levels at all time periods. Significant differences occurred among the groups during the first 4 days (p < 0.05), except at 12 h (p = 0.054). The patients in the CLC and GuttaFlow2 groups did not need to use the prescribed analgesic; however, one patient in the GuttaCore group used it once. Conclusions Postoperative pain levels following root canal therapy were affected by the obturation technique especially first 4 days following obturation.
Keywords: Root canal obturation; Endodontics; Postoperative pain; GuttaCore; GuttaFlow2; Cold lateral compaction; Analgesic intake; Obturation technique